Primary central nervous system lymphomas and related diseases: Pathological characteristics and discussion of the differential diagnosis. Issue 4 (26th November 2015) - Sugita, Yasuo; Muta, Hiroko; Ohshima, Koichi; Morioka, Motohiro; Tsukamoto, Yoshihiro; Takahashi, Hitoshi; Kakita, Akiyoshi
Abstract : Although primary diffuse large B‐cell lymphomas of the CNS are designated as primary CNS lymphomas according to the WHO Classification of Tumours of Haematopoietic and Lymphoid Tissue in 2008, a variety of other lymphomas (Burkitt lymphomas, EBV‐positive diffuse large B‐cell lymphoma of the elderly) and related diseases (lymphomatoid granulomatosis) that are also found in the CNS have been spotlighted in recent years. The histopathology of primary CNS Burkitt lymphomas mimics that of primary diffuse large B‐cell lymphomas of the CNS after steroid administration. Therefore, for correct diagnosis of the involved lymphoma, comprehensive fluorescent in situ hybridization analysis for c‐MYC and BCL2 is recommended in all primary CNS lymphoma cases with aggressive clinical course, multifocal involvement of the CNS, and a high proliferation index. The pathological characteristics of primary CNS EBV‐positive diffuse large B‐cell lymphoma of the elderly have similarities with those of the latency phenotype III, EBV lymphoproliferative disorders that arise in the setting of immunodeficiency. These age‐related lymphomas usually occur in elderly immunocompetent patients, and the incidence of this disease was estimated to range from 4.0% to 13.6% of all primary CNS lymphomas. Shorter overall survival has been reported for patients with this disease. Lymphomatoid granulomatosis (LYG) is a systemic, EBV‐driven, angiocentric and angiodestructive lymphoproliferative disorder. Primary LYG that shows distinct clinicopathological features compared with systemic LYG was recently reported. Finally, this review focuses on the relationship between primary CNS lymphomas and demyelinating diseases, and the concomitant use of intraoperative cytology and frozen sections that are helpful in rapid intraoperative diagnosis.